Future Risks and Fragilities for Financial Stability - Stefano Pagliari; Clive Briault; Alistair Milne; Patricia Jackson; Vicky Pryce; David T. Llewellyn; David Lascelles; Thorsten Beck (SUERF - The European Money and Finance Forum, 2012)
In March 2012 a conference, organised jointly by the ICFR and SUERF, on "Future Risks and Fragilities for Financial Stability", explored what the next pressure points for financial stability might be, how these may arise from the response to the last financial crisis, and how the industry and the regulators can prepare for them. In order to discuss this theme, the conference brought together a select group of academics, industry practitioners and policymakers to discuss a range of connected issues, mainly incentives and market discipline, regulation, competition and shadow banking, and size and structure of business models.
Keywords: G1; G20; G21; G28; G38; 330; Financial Stability; Incentive Structures; Market Discipline; Bank Disclosure Councils; Basel III; Shadow Banking; Regulation; Competition; Bank Business Models; Bankenaufsicht; Bankgeschäft; Basler Akkord; Bankenregulierung; Europa